Pharmacist-Led Optimization of High-Alert Medications in Critical Care Settings - Hadi Mansour Nasser Alreshidi; Alreshidi, Abdullah Ayesh T; Alshilash, Ibrahim Abdulrahman; Mansour Nasser Muhanna Alhamili; Albalawi, Amani Owaidh S; Alasmari, Saeed Abdulrahman S; Batool Saad Almsaudi; Bader Salman Albalawi; Majed Ayyadah Sakarn Alruwaili; Alenezi, Khalaf Alwan T; Fawzan Mohammed Fawzan Alaqil (International Journal of Computational and Experimental Science and Engineering, 2024)
Pharmacist-led optimization of high-alert medications in critical care settings is a crucial component of patient safety and medication management. High-alert medications, which carry a higher risk of causing significant harm if used improperly, require diligent oversight to ensure their safe administration. Pharmacists play a vital role in this process, utilizing their specialized knowledge to assess medication appropriateness, monitor dosing regimens, and identify potential drug interactions. By collaborating closely with healthcare teams, pharmacists can implement evidence-based protocols and recommendations that enhance patient outcomes. Their involvement can lead to the reduction of adverse drug events, streamlined medication reconciliation practices, and improved therapeutic management for critically ill patients. In addition to clinical expertise, pharmacist-led initiatives often include ongoing education and training for healthcare providers about the safe use of high-alert medications. This education encompasses various facets, including understanding the pharmacodynamics and pharmacokinetics of these medications, recognizing the signs of toxicity or therapeutic failure, and employing strategies to mitigate associated risks. By fostering a culture of safety and continuous learning, pharmacists empower the healthcare team to address the complexities of medication management in critical care environments. Ultimately, the integration of pharmacists into critical care teams not only enhances medication safety but also contributes to the overall quality of care provided to vulnerable patient populations.